Identification of dissolved organic matter in raw water supply from reservoirs and canals as precursors to trihalomethanes formation - Charongpun Musikavong (2018)
The characteristic and quantity of dissolved organic matter (DOM) as trihalomethanes precursors in water from the U-Tapao Basin, Songkhla, Thailand was investigated. The sources of water in the basin consisted of two reservoirs and the U-Tapao canal. The canal receives water discharge from reservoirs, treated and untreated wastewater from agricultural processes, communities and industries. Water downstream of the canal is utilized as a raw water supply. Water samples were collected from two reservoirs, upstream and midstream of the canal, and the raw water supply in the rainy season and summer. The DOM level in the canal water was higher than that of the reservoir water. The highest trihalomethane formation potential (THMFP) was formed in the raw water supply. Fourier-transform infrared peaks of the humic acid were detected in the reservoir and canal waters. Aliphatic hydrocarbon and organic nitrogen were the major chemical classes in the reservoir and canal water characterized by a pyrolysis gas chromatography mass spectrometer. The optimal condition of the poly aluminum chloride (PACl) coagulation was obtained at a dosage of 40 mg/L at pH 7. This condition could reduce the average UV-254 to 57%, DOC to 64%, and THMFP to 42%. In the coagulated water, peaks of O-H groups or H-bonded NH, CO of cyclic and acyclic compounds, ketones and quinines, aromatic CC, C-O of alcohols, ethers, and carbohydrates, deformation of COOH, and carboxylic acid salts were detected. The aliphatic hydrocarbon, organic nitrogen and aldehydes and ketones were the major chemical classes. These DOM could be considered as the prominent DOM for the water supply plant that utilized PACl as a coagulant. © 2013 Taylor & Francis Group, LLC.